2022
DOI: 10.1186/s12891-022-06089-9
|View full text |Cite
|
Sign up to set email alerts
|

Collagen and platelet-rich plasma in partial-thickness rotator cuff injuries. Friends or only indifferent neighbours? Randomised controlled trial

Abstract: Background Partial-thickness rotator cuff injuries (PTRCI) are the sum of degenerative, overload, and microtrauma processes. An external supply of collagen and platelet-rich plasma (PRP) could potentially counteract the deterioration of degenerative tendinopathy. This study aimed to compare the effectiveness of collagen with PRP, PRP alone, and collagen alone in the treatment of PTRCI. Methods Ninety patients with PTRCI were randomised and treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Multiple studies using tendon-like cell models have consistently shown that the combination of collagen and PRP exerts synergistic effects. The addition of various PRP products resulted in increased cell proliferation, confirming the positive impact of this combination 31 . The benefits of collagen injections are confirmed by the findings of the present systematic review, coherently with the results of a recent RCT 35 .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Multiple studies using tendon-like cell models have consistently shown that the combination of collagen and PRP exerts synergistic effects. The addition of various PRP products resulted in increased cell proliferation, confirming the positive impact of this combination 31 . The benefits of collagen injections are confirmed by the findings of the present systematic review, coherently with the results of a recent RCT 35 .…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the Level of Evidence, 5 studies were level I RCTs 30,31,34,37,38 ; 5 level III PCC studies 7,8,32,33,42 ; and 1 level IV prospective case-series study 36 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations